2020
DOI: 10.1021/acscatal.0c02755
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Alkene Hydroboration/Palladium-Catalyzed Migratory Suzuki–Miyaura Cross-Coupling

Abstract: Chain-walking is a powerful approach toward the functionalization of C−H bonds remote to a functional group. Whereas various Pdcatalyzed migratory cross-couplings have been developed in the past years, the design of an efficient migratory version of the popular Suzuki−Miyaura cross-coupling has remained elusive. The current article reports a one-pot procedure consisting of alkene hydroboration and migratory Suzuki−Miyaura coupling of the resulting alkylboronic acid intermediate. A high regioselectivity for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 81 publications
1
13
0
Order By: Relevance
“…Unsurprisingly, the reaction of Z - 1a proceeded efficiently to afford aminoalcohol 2a in 74% yield (eq 2), suggesting the configuration of alkenes did not interfere with the chain walking process. Moreover, a deuterated reaction was carried out with allylic amine 1b and DBpin, and the deuterium was found to be incorporated along the alkyl chain (eq 3), which is consistent with the chain walking mechanism (β-hydride elimination and reinsertion). , The deuterium incorporation at the α-position of D - 2b indicated that an enamine might be an intermediate in the isomerization via the β-hydride elimination. Consequently, enamine 1ah was prepared and treated with the standard reaction conditions.…”
supporting
confidence: 62%
“…Unsurprisingly, the reaction of Z - 1a proceeded efficiently to afford aminoalcohol 2a in 74% yield (eq 2), suggesting the configuration of alkenes did not interfere with the chain walking process. Moreover, a deuterated reaction was carried out with allylic amine 1b and DBpin, and the deuterium was found to be incorporated along the alkyl chain (eq 3), which is consistent with the chain walking mechanism (β-hydride elimination and reinsertion). , The deuterium incorporation at the α-position of D - 2b indicated that an enamine might be an intermediate in the isomerization via the β-hydride elimination. Consequently, enamine 1ah was prepared and treated with the standard reaction conditions.…”
supporting
confidence: 62%
“…Aside from the product selectivity, the overall reaction speed of only 10 min at room temperature is unprecedented also (as compared to 24 h reaction times in Ni‐based couplings or 48 h in Pd‐based protocols) [4–6] . Since the chain walking relies on the analogous elementary steps as other Pd‐based protocols (i.e.…”
Section: Figurementioning
confidence: 99%
“…[5] In this context Baudoin recently reported a notable advance which relied on Pd-catalysis and could tolerate ortho-substituents, albeit requiring high temperatures (120 8C) during 48 hours and a terminal blocking group in the substrate to prevent alternative products (see Figure 1 B). [6,7] Ortho-fluorinated 1,1-diaryl alkane motifs were not showcased. These motifs are of distinct importance, being featured in numerous bioactive compounds [8] with anti-HIV, anti-fungal or anti-blood clotting activities, for example.…”
mentioning
confidence: 99%
“…Electronic variations of the aryl group of the coupling partner are well tolerated, ranging from electron donating tert-butyl (9) to electron withdrawing trifluoromethyl-substituted aryl moieties (4,10). Notably, the ortho-methyl and -isopropyl groups (6,7) did not affect the reaction speed and efficiency, and only minimally effected the product selectivity (branched vs. linear). While as large substituents as isopropyl have so far not been showcased, the smaller ortho-methyl substituent (as in 6) could otherwise only be tolerated under much harsher conditions, such as Baudoins recent protocol, [6] requiring 120 8C and 48 h reaction time or Zhus protocol, [5c] needing 80 8C for 24 h. Potentially coordinating functionalities such as the cyano group ( 13) did not impede the reaction.…”
mentioning
confidence: 99%
See 1 more Smart Citation